2018
DOI: 10.2147/copd.s149404
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with appropriate inhaler use in patients with COPD – lessons from the REAL survey

Abstract: BackgroundNonadherence to medication and incorrect use of inhalers represent significant barriers to optimal disease management of patients with chronic obstructive pulmonary disease (COPD). Thus, health care professionals (HCPs) play a critical role in educating their patients on appropriate inhaler use and in ensuring medication adherence. However, many patients do not receive appropriate inhaler training or have not had their inhaler technique checked.MethodsThe Real-life Experience and Accuracy of inhaLer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
90
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 18 publications
4
90
1
3
Order By: Relevance
“…Such differences may be linked to the larger mouthpiece of the Breezhaler Ò as well as to the ability for patients to visually confirm if any powder is left in the capsule after each actuation. These results were confirmed in the recent Real life Experience and Accuracy of inhaLer use (REAL) survey conducted in patients with COPD, which gathered insights into real-life inhaler use by patients and healthcare providers, device attributes, and training [77]. The majority of patients using Breezhaler Ò reported either being very confident or confident of having taken a full dose, which was higher than those using Genuair Ò , Ellipta Ò , and Respimat Ò .…”
Section: Preference For Laba/lama Inhaler Devicessupporting
confidence: 55%
See 2 more Smart Citations
“…Such differences may be linked to the larger mouthpiece of the Breezhaler Ò as well as to the ability for patients to visually confirm if any powder is left in the capsule after each actuation. These results were confirmed in the recent Real life Experience and Accuracy of inhaLer use (REAL) survey conducted in patients with COPD, which gathered insights into real-life inhaler use by patients and healthcare providers, device attributes, and training [77]. The majority of patients using Breezhaler Ò reported either being very confident or confident of having taken a full dose, which was higher than those using Genuair Ò , Ellipta Ò , and Respimat Ò .…”
Section: Preference For Laba/lama Inhaler Devicessupporting
confidence: 55%
“…The majority of patients using Breezhaler Ò reported either being very confident or confident of having taken a full dose, which was higher than those using Genuair Ò , Ellipta Ò , and Respimat Ò . However, this study also identified a low incidence of patient training and monitoring by healthcare providers for correct inhaler use [77]. In the recently reported INHALATOR study, a significantly greater proportion of patients expressed preference for Breezhaler Ò than for Respimat Ò (57.1% versus 30.1%) [78].…”
Section: Preference For Laba/lama Inhaler Devicesmentioning
confidence: 73%
See 1 more Smart Citation
“…O manejo correto dos dispositivos inalatórios é fundamental para deposição pulmonar eficiente dos agentes farmacológicos, e consequentemente, para a efetividade do tratamento da doença. 1,2 Entretanto, muitos pacientes podem não utilizar corretamente os inaladores. A técnica inalatória incorreta é associada a desfechos negativos, pior qualidade de vida e maior utilização dos recursos de saúde em pacientes com DPOC.…”
Section: Comunicação Breveunclassified
“…A técnica inalatória incorreta é associada a desfechos negativos, pior qualidade de vida e maior utilização dos recursos de saúde em pacientes com DPOC. [1][2][3][4] Dados sobre o manuseio dos dispositivos inalatórios entre indivíduos com DPOC são escassos em nosso meio, sobretudo, no contexto da prática clínica. O objetivo do estudo foi avaliar o domínio da técnica entre pacientes com DPOC grave em uso de dois diferentes dispositivos inalatórios (Respimat ® e Diskus ® ).…”
Section: Comunicação Breveunclassified